Analysis of Water Hardness in Lapindo Mud Sources: Identification of Ca²⁺ and Mg²⁺ using the EDTA Method as a Science Learning Medium - Siti Aminatus Sholeha Sholeha; Della Septya Feransyah; Fiza Alfa'i Robiyah; Frista Alfidya Hafidz Zain (PT. Komunitas Peneliti Alinea, 2025)
Water hardness refers to water that has a high calcium and magnesium ion content, which affects water quality. Hard water can cause several side effects, one of which is health problems that can trigger kidney stones. This study was conducted with the aim of determining the level of hardness contained in Lapindo mud water, as well as providing information on the methods used to accurately test water hardness levels. The method used was a laboratory experiment conducted by changing the independent variable to see its impact on the dependent variable. This research was conducted on 14 August 2025 at the Household Chemistry Laboratory of the Science Education Study Programme at Trunojoyo University, Madura, which produced a total hardness of 379.4 mg/L in the sample. The results obtained show that the method used is very effective in identifying the level of water hardness and provides valid data to support the treatment of water to make it suitable for consumption.